Facilitating Language Acquisition Using Computer Assisted Language Learning - Cobb, Kimberly (Valdosta State University, 2001)
This paper discusses an action research project that examines the effects and outcomes of using computer assisted language learning (CALL) to facilitate second language acquisition with ESOL students. Nine students who were enrolled in an ESOL 10th grade English class participated in this study. These students worked for approximately three days a week interacting with an ESOL component of an interactive CALL program. Module scores, dialog/conversation analyses, and teachers' reports showed that the ESOL students made progress in their acquisition of the English language after approximately five weeks of CALL instruction. In order to investigate whether their progress in acquisition of the language was evident in other modes of language production, students engaged in small and large group discussions, during which their conversational dialog was analyzed. They also wrote various types of compositions in which they applied language skills. The quantitative and qualitative analysis of their products revealed a marked improvement in the students' manipulation of the English language. The results concluded that computer assisted language learning can enhance students' motivation and confidence in using the English language and can improve language acquisition in ESOL students.
Keywords: CALL; Second language; ESOL students; Educational technology; Computer-assisted instruction; Teaching--Aids and devices